THE EFFECT OF E-SERVICE QUALITY ON REPURCHASE INTENTION THROUGH E-TRUST AND E-SATISFACTION (STUDY OF B2B EMOS MARKETPLACE’S USER IN MALANG) - Firda Meisaroh; Sudarmiatin Sudarmiatin; Agus Hermawan (Journal of Management and Informatics, 2022)
EMOS Marketplace as one of the business to business (B2B) e-commerce which is in great demand by customers,especially pharmacies, clinics and private hospitals. Along with the development of technology in the industrialera 5.0, where customers become decision makers and can determine for themselves which distributor to chooseto buy the pharmaceutical products needed at this time. This research is a quantitative research using a descriptiveresearch design and path analysis techniques. There are consisting of 200 pharmacists that become respondentsby using Slovin formula approach. The results of this study indicate that variables E-Service Quality, E-Trust, E-Satisfaction and Repurchase Intention have a positive and significant. Based on the results of this study,suggestions that researchers can convey to EMOS Marketplace to continues improvement include increasingcustomer security standards, adding a product search feature based on manufacturers and WhatsApp notificationsto find out order status. Hopefully EMOS Marketplace always create continuous innovation (continuesimprovement) in terms of service. So that customers will feel trusted and satisfied with EMOS Marketplace.